2021
DOI: 10.1111/cla.12475
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenome phylogeny reveals Indochina Peninsula origin and spatiotemporal diversification of freshwater crabs (Potamidae: Potamiscinae) in China

Abstract: The Asian potamid subfamily Potamiscinae is the most species-rich group of primary freshwater crabs in the world, and a large number of these (318 species in 52 genera) are found in China where they exhibit a remarkably high rate of endemism. However, the evolutionary history and phylogenetic relationships of this subfamily is still poorly understood and the hypothesis that the Chinese potamids originated in the Indochina Peninsula has yet to be tested using a modern phylogeographic reconstruction and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Among them, S. chishuiense and S. yaanense formed one clade while S. wushanense , S. kenliense , and S. exiguum clustered one clade (Figure 5). The nonmonophyly of the Sinopotamon crabs had been widely reported (Ji, 2016) and the Sinopotamon maintained a closer relationship with the Vadosapotamon , Latopotamon , and Tenuilapotamon (Pan et al, 2022; Zhang et al, 2020), which was also consistent with Sinopotamon being most closely related to Tenuilapotamon in our study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Among them, S. chishuiense and S. yaanense formed one clade while S. wushanense , S. kenliense , and S. exiguum clustered one clade (Figure 5). The nonmonophyly of the Sinopotamon crabs had been widely reported (Ji, 2016) and the Sinopotamon maintained a closer relationship with the Vadosapotamon , Latopotamon , and Tenuilapotamon (Pan et al, 2022; Zhang et al, 2020), which was also consistent with Sinopotamon being most closely related to Tenuilapotamon in our study.…”
Section: Resultssupporting
confidence: 92%
“…The extrusion of the Cenozoic Indian and Pacific plates onto the Asian and European continents and the associated orogeny led to the uplift of numerous mountain ranges of different elevations and spans within China (Deng et al, 2016; Guo, 1994; Sanzhong et al, 2019; Zhang, 1993). Therefore, the weak dispersal capacity and the geographic isolation factors such as mountain systems and water systems may have led to the evolution of Sinopotamon species diversity in the China, and that may also be an important reason for its nonmonophyletic nature (Chen et al, 2012; Pan et al, 2022; Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…9 ). The phylogenetic relationship showed that the genus Huananpotamon is monophyletic and belongs to the “South China-adjacent Islands” clade ( Pan et al 2022 ) (Fig. 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 43 sequences from the ingroup and outgroup taxa were used in the phylogenetic analyses, including 33 downloaded sequences (Table 1 ). Pan et al (2022) showed that the genus Huananpotamon nested within the “South China-adjacent Islands” clade; therefore, closely related genera from the same clade, in particular the taxa of closely related genera from Fujian, Guangdong, and Jiangxi, and some others from adjacent islands, were included for the present phylogenetic analyses (Table 1 ). For the genus Huananpotamon , eight species from the adjacent area of the Wuyishan National Park were included, of which four species are morphologically most similar to H. koatenense (Table 1 ; Fig.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation